LITHEUM. A web-based lighting and thermal urban model for city energy assessment - Rodríguez-Álvarez, Jorge; Rodríguez-Luaces, Miguel Ángel; Varela-Rodeiro, Tirso; Alvaredo-López, Natalia; Lamas-Sardiña, Víctor (Sustainable cities and society, 2025)
•Litheum is an interactive online Urban Building Energy Modeling tool.•Maps citywide energy demand using EN 52016-based calculation methods.•Custom algorithms account for detailed building and urban form features.•Lightweight tool that runs directly in a standard web browser.•Validated in three cities and refined through stakeholder feedback. This study presents Litheum (LIghting and THErmal Urban Model), an online urban building energy modelling (UBEM) tool that integrates morphological sensitivity analysis with interactive scenario development. By leveraging Geographic Information Systems and open-source technologies, the model addresses the accessibility challenges of previous UBEM tools, offering an intuitive web-based application suitable for diverse users, from homeowners to planners and policymakers, without requiring prior energy modelling expertise. Litheum applies a novel algorithm to calculate solar obstruction, optimizing computational requirements while capturing the spatial and temporal dynamics of urban contexts, an area where data-driven models often fall short. The energy calculation methods follow the EN ISO 52016–1 standard, balancing precision, flexibility, and reproducibility for large-scale applications. Unlike detailed dynamic building simulation tools, Litheum is optimized for urban energy planning and policy development. Pilot studies in three Spanish cities—Pontevedra, A Coruña, and Madrid—demonstrated the model's adaptability across varying urban scales. Feedback informed enhancements, including a solar control mode functionality for warmer climates. The online platform's design enables seamless interaction and rapid deployment in diverse urban settings. Future efforts will focus on expanding the platform's deployment in additional cities, integrating artificial intelligence to infer key building characteristics, such as glazing ratios, to improve robustness and processing efficiency. Litheum exemplifies the potential of open-source UBEM tools to facilitate energy assessment, fostering widespread adoption and better informed planning decisions.